HLA-E Binding Peptide as a Potential Therapeutic Candidate for High-Risk Multiple Myeloma - Yang, Ying; Liu, Zhuogang; Wang, Hongtao; Zhang, Guojun (Frontiers in Oncology, 2021)
Human leukocyte antigen-E (HLA-E) has been putatively associated with the pathogenesis of multiple myeloma (MM). Our study first showed HLA-E was differentially expressed on MM and normal plasma cells (39.27±27.01 and 11.28±0.79, respectively). Based on the median value of HLA-E expression, we further stratified MM patients into high and low-expression groups, and then found high expression of HLA-E was correlated with advanced ISS stage (p=0.025) and high-risk cytogenetics risk stratification (p=0.000) by the Pearson Chi-square test, suggesting that HLA-E could be considered as a biomarker for high-risk MM. Furthermore, peptide 3 (P3) from our previous study was confirmed to possess a high affinity to HLA-E positive MM cells. Taken together, HLA-E could be considered as a new marker and candidate treatment target for MM, while peptide P3 may act as a potential treatment choice for targeting MM cells.